(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current situation shows that the manager of Micro, Small and Medium Enterprises (MSMEs) have a low ability to calculate the cost of goods manufactured. Low ability is shown by means of simple calculations without being based on theoretical knowledge required as a basis for calculation. To improve the skills of MSME managers in determining the cost of goods manufactured, training is given using technical guidance methods with mentoring programs. This study aims to determine the benefits of these training activities. The research method used is descriptive with a comparative approach, namely comparing the conditions before and after the training activities. The results showed that training activities can provide benefits to improve the skills of managers in determining the cost of goods manufactured